LOCAL WISDOM VALUES IN THE ARCHITECTURE OF GEDUNG SATE AS CULTURAL HERITAGE AND EDUCATION FOR THE YOUNG GENERATION - Zahra Khurulia Aini; Gita Pebrianti; Sulistiani; Wina Fauziyah; Tetep (Journal Civics And Social Studies, 2024)
Gedung Sate, as an architectural icon of West Java, integrates elements of local wisdom with Indo-European architectural styles, resulting in a harmony of aesthetics and culture. This study aims to identify the local wisdom embodied in its architecture and analyze the cultural values within it to ensure their interpretation and preservation. Utilizing a qualitative approach through literature review, interviews, and direct observation, the findings reveal that Gedung Sate reflects values such as communal cooperation, respect for nature, and cultural acculturation through architectural elements like temple-inspired facades, its orientation toward Mount Tangkuban Perahu, and the use of local materials. This study underscores the role of Gedung Sate as a cultural heritage symbol that must be preserved through innovative education to strengthen the identity of younger generation. Keywords: Architecture, Culture, Gedung sate, Youth, Local Wisdom.